Production of Soybean Varieties under Saturated Soil Culture on Tidal Swamps - Munif Ghulamahdi; Maya Melati; Danner Sagala (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2009)
Saturated soil culture (SSC) is a cultivation technology that gives continuous irrigation and maintains water depth constantly and makes soil layer in saturated condition. By keeping the water-table constantly, soybean will be avoided from negative effect of inundation on soybean growth because soybean will acclimatize and improve its growth. The objective of the research was to study the response of soybean varieties under saturated soil culture on tidal swamps. The research was conducted at Banyu Urip of  Tanjung Lago Sub District, Banyuasin District, South Sumatera Province, Indonesia from April to August 2009. The experiment was arranged in a split plot design with three replications. The main plot was water depth in the furrow consisted of without watering, 10, 20, 30, 40 cm under soil surface (uss). The subplot was soybean variety consisted of Tanggamus, Slamet, Willis, and Anjasmoro. The result showed that the interaction between varieties and water depth significantly affected growth and seed production, except pod numbers/plant. The values of all variables were higher under SSC compared to those cultivated without watering (control), but varieties responded to SSC differently. The highest seed production was obtained from Tanggamus with 40 cm uss, i.e. 4.83 ton/ha but it was not significantly different from those at water depth 20 (4.63 ton/ha) and 30 cm uss (4.71 ton/ha). However, technically and economically, 20 cm uss was the most appropriate water depth for soybean production on tidal swamps.   Key words: Glycine max L. (Merr.), water management, water table